2015
DOI: 10.4028/www.scientific.net/amm.794.262
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytes for Sustainable Laser-Chemical Machining of Titanium, Stellite 21 and Tool Steel X110CrMoV8-2

Abstract: Laser-chemical micro structuring offers a possibility to process particular metals nearly without any mechanical or thermal stress. The required electrolyte depends on the respective chemical composition of the specific metal. The presented results demonstrate the possibilities for laser-chemical machining of titanium, Stellite 21 and tool steel X110CrMoV82 for use in medical applications and micro tool manufacturing with respect to the engineering requirements. Furthermore, first results are shown depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…With respect to the electrolyte solution the self-passivation of the used material is usually required in laser chemical machining. The LCM of Stellite 21 in phosphoric acid environment shows, as expected, similar behavior compared with other self-passivating materials, such as titanium [23], memory shape alloys (e.g. nickel-titanium alloys) [12] and stainless steel [24].…”
Section: Influence Of Self-passivation Property On the Machining Qualitysupporting
confidence: 75%
“…With respect to the electrolyte solution the self-passivation of the used material is usually required in laser chemical machining. The LCM of Stellite 21 in phosphoric acid environment shows, as expected, similar behavior compared with other self-passivating materials, such as titanium [23], memory shape alloys (e.g. nickel-titanium alloys) [12] and stainless steel [24].…”
Section: Influence Of Self-passivation Property On the Machining Qualitysupporting
confidence: 75%
“…The LCM-induced surface irregularities are related to two different effects. The first one is due to the used Gaussian laser beam profile, which results in an inhomogeneous removal even with closed hatching distance [21]. The second effect is related to the unequal chemical dissolution rates of the different alloy elements with respect to the used electrolyte solution [22] as well as the dependence of the achievable surface quality on the micro structure (grain size and element distribution) [15].…”
Section: Discussionmentioning
confidence: 99%
“…These ensure the highest efficiency, as was demonstrated by Nowak et al [Now96] and Stephen et al [Ste11]. However, more environmentally friendly electrolytes such as sodium chloride (NaCl) and sodium nitrate (NaNO 3 ) solutions were tested and compared with the acidic solutions [Hau15a]. The results will be discussed in more detail in Sect.…”
Section: Influence Of the Electrolytementioning
confidence: 91%
“…Thereby, the amount and quality of the material dissolution is dependent on the chemical reactivity of the material elements. In [Hau15a] it was shown that the LCM of titanium in a 5 molar H 3 PO 4 results in up to 39% higher removal rates and up to 30% deeper cavities in comparison with Stellite 21. This can be explained by the higher electronegativities of cobalt (63%) and chromium (25%), as the main elements in Stellite 21, in comparison with that of titanium.…”
Section: Influence Of the Materialsmentioning
confidence: 99%
See 1 more Smart Citation